SYNTHESIS OF 1,3-DISUBSTITUED-2,3-DIHYDRO-1H-NAFT[1,3] OXAZINE COMPOUNDS - Ozturkcan, S. Arda; Turgut, Zuhal (YILDIZ TECHNICAL UNIV, 2009)
In this study, Betti's classical procedur[1], a Mannich-type aminoalkylation reaction of 2-naphtol with furan2-, furan-3-, thiphene-3-, pyridine-4-and naptalene-2-carbaldehydes was applied in the presence of ammonia. 1,3-disubstituted-2,3-dihydro-1H-naphtoxazines were synthesized The structures of the obtained new compounds have been clarified by spectroscopic methods (FTIR, H-1 NMR, C-13 NMR and MS) and confirmed with elemental analysis results.
Keywords: Heterocyclic compounds; 1,3-Oxazine compounds; ring closure; Engineering